Refractory Haematuria Resulting From Peritoneal Dissemination of Metastatic Gastric Cancer: Radiation Therapy For A Nodule Infiltrating The Urinary Bladder - Ishibashi, Naoya; Maebayashi, Toshiya; Aizawa, Takuya; Sakaguchi, Masakuni; Abe, Osamu; Matsui, Tsuyoshi; Watanabe, Megumu (Urology Journal, 2017)
Bladder metastases from remote primary sites are rarely reported. We present a case of haematuria caused by infiltrationof the urinary bladder wall by a nodule resulting from peritoneal dissemination of a primary gastric tumour.The nodule was detected by computed tomography, magnetic resonance imaging and cystoscopy. Transarterialembolization or haemostasis could not be performed because of the haematuria, thus the vesical bleeding was treatedwith a low irradiation dose of 3 Gy/fraction for a total of 30 Gy administered to the dome of the urinary bladder.No adverse effects occurred, and the gross haematuria and nodule resolved within 1 week. Thus, radiotherapyshould be considered for treatment of visceral bleeding caused by peritoneal dissemination of gastric cancer whenother methods of haemostasis cannot be performed.